PARENTING STYLES IN SHAPING THE CHILDREN'S SOCIAL CARE CHARACTER DURING THE PANDEMIC - Sri Rizqi Hasanah; Ristiyani; Muhammad Noor Ahsin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to analyze the parenting styles applied by parents in shaping the character of social care and its obstacles. This research was qualitative research with a case study approach conducted in Desa Ngliron, Kecamatan Randublatung, Kabupaten Blora. The research subjects were parents and children. Data collection techniques were in the form of observation, interviews, documentation, and notes. Interviews were conducted with parents who applied parenting, children, and the community. Data analysis techniques used data collection, data reduction, data presentation, and drawing conclusions. The results showed that parents in Desa Ngliron applied democratic and permissive parenting in shaping the character of social care for the majority of children. The parents applied democratic parenting to children by providing understanding, habituation, exemplary, and spontaneous activities, so that children had a character of social care such as being polite, friendly, sharing, and helping others. Parents who applied permissive parenting tended to pay less attention to their children and did not apply rules, which made them aggressive and selfish. There were obstacles faced by parents in shaping the character of social care for children, namely parents' busyness, lack of parental understanding, children’s character, and technology.